UNPACKING THE DRIVERS OF EMPLOYEE PRODUCTIVITY IN THE SECRETARIAT REGIONAL COUNCIL OF PEOPLE'S REPRESENTATIVES (DPRD): THE ROLE OF COMPETENCE, WORK ATTITUDE, AND COMMUNICATION - CASLIYAWATI; Ellin Herlina (PT. Berkah Digital Teknologi, 2023)
Purpose: This study aims to determine the effect of competence, work attitude and communication on employee productivity at the secretariat of the DPRD of Indramayu RegencyResearch Methodology: This research uses a survey method. The survey method is used to solve actual large-scale issue problems with very large populations, so a large sample size is required.Results: There is a partial influence of competence on the productivity of the DPRD Secretariat staff in Indramayu Regency. There is a partial effect of work attitude on the productivity of the DPRD secretariat staff in Indramayu Regency. There is a partial effect of communication on the productivity of the DPRD Secretariat staff in Indramayu Regency. There is an influence of Competence, Work Attitude, and Communication simultaneously on the productivity of the Secretariat Employees of the DPRD of Indramayu RegencyLimitations: this research is not free from limitations, namely the research object only focuses on the Secretariat of the DPRD of Indramayu RegencyContribution: This research will contribute to the field of human resources in the development of work productivity as well as communication, work attitudes and competencies